Trial by media: Why victims and activists seek a parallel justice forum for war crimes. (December 2020) - Rae, Maria
When the brutal Sri Lankan conflict ended, victims and activists launched global war crimes cases against the state alongside successful media campaigns. Although these justice claims never progressed to a court of law, they were heard, through the media, by the court of public opinion. This article considers to what extent a 'trial by media' might have the potential to provide a parallel justice forum. It questions how activists and victims view the role of the media in seeking justice. It finds they perceive the media's key functions are to expose crimes, bear witness to crimes, name perpetrators, influence public opinion and apply pressure on legal and political institutions to respond to human rights abuses. However, victims and activists also recognise the media is limited in delivering justice. Therefore, this article argues a trial by media should be conceived of more as an accountability mechanism that has the capacity to draw attention to the shortcomings of official legal responses and processes.